Beliefs about justification for knowing when ethnic majority and ethnic minority students read multiple conflicting documents. Issue 4 (20th April 2016) - Strømsø, Helge Ivar; Bråten, Ivar; Anmarkrud, Øistein; Ferguson, Leila E.
Abstract : We examined the role of justification for knowing beliefs in learning and comprehension when ethnic majority and ethnic minority students from the same school classes read five conflicting documents on the scientific issue of sun exposure and health. Results showed that the more ethnic minority students trusted scientific authorities and the less they relied on personal opinion when validating knowledge claims in the domain of science, the more they learned from and the better they comprehended the documents. In contrast, justification for knowing beliefs did not seem to play a role in learning and comprehension among ethnic majority students. These results may reflect that the documents represented more of a challenge to the ethnic minority students, with justification beliefs affecting learning and comprehension processes to a greater extent when the task is perceived as an ill-structured problem. This study is probably the first to indicate different relationships between various justification beliefs and performance in different language and cultural groups, having theoretical as well as educational implications.